2008
DOI: 10.1002/hfm.20132
|View full text |Cite
|
Sign up to set email alerts
|

Comparing stationary standing with an intermittent walking posture during assembly operations

Abstract: The purpose of this investigation was to evaluate two different standing postures, intermittent walking (dynamic) and stationary, on 11 volunteers. While performing the activity in a stationary posture, volunteers worked barefoot for 25 minutes at a particular workstation, taking up to five passive breaks. The dynamic standing postural activity was similar in every respect with the exception of the nature of the breaks that were spent walking from one workstation to the other. Foot pressure was analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…5, Table 1). These findings are in line with other studies in which they suggested that dynamic standing or more variation in lower limb movements and muscles activity leads to less discomfort and swelling in the lower extremities during prolonged standing (Balasubramanian et al, 2008(Balasubramanian et al, , 2009Lin et al, 2012a).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…5, Table 1). These findings are in line with other studies in which they suggested that dynamic standing or more variation in lower limb movements and muscles activity leads to less discomfort and swelling in the lower extremities during prolonged standing (Balasubramanian et al, 2008(Balasubramanian et al, , 2009Lin et al, 2012a).…”
Section: Discussionsupporting
confidence: 93%
“…Active standing is classified as the use of an unstable standing surface which requires the subject to engage in more body movement (lower limb in particular) to maintain an upright standing posture. A more dynamic situation during standing can lead to an increase in the muscle activity level; Furthermore it can increase the variation in the muscle activity, which might be useful for blood circulation and reduction of discomfort (Srinivasan and Mathiassen, 2012;Balasubramanian et al, 2008Balasubramanian et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…The active exercises required during the break did not have an advantage over passive breaks; however, this result may be due to the duration of the activity. Dynamic/walking interventions have attenuated effects compared with a more static standing posture (Balasubramanian, Adalarasu, & Regulapati, 2008, 2009; Garcia et al, 2016). Hence, the integration of dynamic interventions may have a benefit if done during the standing period instead of the break.…”
Section: Discussionmentioning
confidence: 99%
“…Many service occupations, such as health care workers (Meijsen & Knibbe, 2007) and sales personnel (Pensri, Janwantanakul, & Chaikumarn, 2009), as well as many manufacturing jobs (Balasubramanian, Adalarasu, & Regulapati, 2008; Messing, Stock, Côté, & Tissot, 2015) require working in a standing posture. Standing work is very common in diverse workplaces around the world.…”
Section: Introductionmentioning
confidence: 99%